2000
DOI: 10.1128/mcb.20.8.2670-2675.2000
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Heat Shock Factor 1 Reveals an Essential Role in the Ubiquitin Proteolytic Pathway

Abstract: Inhibition of proteasome-mediated protein degradation machinery is a potent stress stimulus that causes accumulation of ubiquitinated proteins and increased expression of heat shock proteins (Hsps). Hsps play pivotal roles in homeostasis and protection in a cell, through their well-recognized properties as molecular chaperones. The inducible Hsp expression is regulated by the heat shock transcription factors (HSFs). Among mammalian HSFs, HSF1 has been shown to be important for regulation of the heat-induced st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
79
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 54 publications
(65 reference statements)
13
79
1
Order By: Relevance
“…Because HSF1 induces Hsp70i and Hsp25 gene expression in response to heat stress, it has been suggested that HSPs may function in a negative feedback mechanism to return HSF1 to its inactive monomeric state (12,13). However, in the present study, ectopic transfection of HSP25 or HSP70i in RIF cells increased the expression of endogenous HSPs, such as HSP25 and HSP70i, through activation of HSF1.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Because HSF1 induces Hsp70i and Hsp25 gene expression in response to heat stress, it has been suggested that HSPs may function in a negative feedback mechanism to return HSF1 to its inactive monomeric state (12,13). However, in the present study, ectopic transfection of HSP25 or HSP70i in RIF cells increased the expression of endogenous HSPs, such as HSP25 and HSP70i, through activation of HSF1.…”
Section: Discussioncontrasting
confidence: 65%
“…In recent years, a conceptual framework for stress-induced activation and feedback repression of HSF1 has emerged (3,12,13). However, our recent study indicated that, in RIF cells that have relatively low HSP25 and inducible HSP70 (HSP70i) expressions, HSP25 or HSP70i mutually coregulated each other and increased their own protein expression through HSF1 activation (14).…”
mentioning
confidence: 99%
“…HSF1 deficiency dramatically prevented the induced expression of Hsp25 and Hsp70 after proteotoxic stress. This was in agreement with previous works showing that HSF1 is the major factor involved in proteotoxic response and that it could not be compensated by HSF2 alone (Pirkkala et al, 2000). As HSP25 and HSP70 promote cellular survival by preventing protein aggregation, facilitating refolding and directly inhibiting apoptotic signaling (Beere et al, 2000;Bruey et al, 2000), Hsf1 À/À cells lacked an important protective mechanism, which could explain the observed reduction in cell survival.…”
Section: Discussionsupporting
confidence: 92%
“…However, inhibition of the proteasome activates both HSF1 and HSF2 (Kawazoe et al, 1998). Proteasome inhibition leads to the accumulation of misfolded proteins and consequently induces expression of all the major HSPs (Bush et al, 1997), but Pirkkala et al (2000) clearly showed that HSF1, but not HSF2, has a key role in this induction. Nevertheless, to add to the complexity of this proteotoxic response, our group showed that an HSF1/HSF2 heterocomplex was present on the promoter of the chaperone gene clusterin, following proteasome inhibition (Loison et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…HSPs belong to the family of chaperone proteins and are important in both refolding misfolded proteins and directing proteins toward proteasomal degradation (23)(24)(25). HSPs can be protective in several neurodegeneration models (26 -29), and recent data in the fly model suggest that overexpression of the molecular chaperone Hsp70 protects against ␣-synuclein-induced degeneration (26,30).…”
mentioning
confidence: 99%